PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING PADA MATERI IMPULS DAN MOMENTUM TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS X SMA NEGERI 1 SENTAJO RAYA KUANSING - Randes Oktazen; Fakhruddin Fakhruddin; Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study was aimed to determine students cognitive study result by the application of guided inquiry learning model. This study was conducted in SMAN 1 Sentajo Raya Kuansing. This study was a quasi experimental using intact group comparison design. The population in this study was student of X MIPA class in SMAN 1 Sentajo Raya Kuansing. Sample on this study obtained from two classes of population based on homogeneity test and the sample was chooseen randomly so that experiment and control classed could be obtained. The data was collected by using cognitive study result test after guided inquiry model was applied in experiment class and conventional learning was applied in control class. The data was analize by using descriptive and inferential analysis. This study showed that the average number of students absorption ability which guided inquiry model was applied 81,05% and 72,56% for the conventional learning. It can be concluded that the application of guided inquiry learning model could enchace students’ cognitive study result on impuls and momentum material at X class SMAN 1 Sentajo Raya kuansing.Keywords : guided inquiry, cognitive study result, impuls and momentum